2010
DOI: 10.1016/j.infbeh.2009.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Relations among temperament, parenting and problem behavior in young children

Abstract: The first objective of this study was to investigate which aspects of temperament are related to externalizing problem behavior and which aspects are related to internalizing problem behavior. The second objective was to investigate how parenting influences the link between temperament and problem behavior. The sample included 89 two-parent families and their firstborn 36-month-old children, and 81 day care and preschool playgroup teachers. Mothers, fathers and teachers filled in questionnaires and home observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
64
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 46 publications
10
64
1
5
Order By: Relevance
“…In the current study, we found moderate-sized associations, with children high on effort control and low on negative affect showing less maladjustment. These direct associations between temperament and behavioral/emotional problems corresponded with what has been found in many past studies (Karreman, de Haas, van Tuijl, van Ahen, & Deković, 2010; Olson, Sameroff, Kerr, Lopez, & Wellman, 2005; Putnam, Sanson & Rothbart, 2002). …”
Section: Discussionsupporting
confidence: 89%
“…In the current study, we found moderate-sized associations, with children high on effort control and low on negative affect showing less maladjustment. These direct associations between temperament and behavioral/emotional problems corresponded with what has been found in many past studies (Karreman, de Haas, van Tuijl, van Ahen, & Deković, 2010; Olson, Sameroff, Kerr, Lopez, & Wellman, 2005; Putnam, Sanson & Rothbart, 2002). …”
Section: Discussionsupporting
confidence: 89%
“…It is noteworthy that across the reviewed literature there is little consistency in which aspects of maternal and paternal rearing behaviour differentially influence anxiety symptoms in the child. For example, parental over control as a predictor of child anxiety symptoms has been shown to be more important in mothers than fathers (Hudson, Comer, & Kendall, 2008), more important in fathers than mothers (van der Bruggen, Stams, Bögels, & Paulussen-Hoogeboom, 2010), and equally as important in mothers and fathers (Karreman, et al, 2010). One obvious next step is to repeat the current study looking at specific, theoretically-driven, aspects of parenting.…”
Section: Discussionmentioning
confidence: 87%
“…There are many studies in which rearing characteristics other than parental anxiety in both fathers and mothers predict child anxiety symptoms, for example: overprotection (Edwards, et al, 2010), parental control (van der Bruggen, Bögels, & van Zeilst, 2010) and negative control (Karreman, de Haas, van Tuijl, van Aken, & Dekovic, 2010). There are other explanations too, for example:…”
Section: Discussionmentioning
confidence: 99%
“…Effortful control reflects the degree to which children engage in inhibitory control such as stopping behavior and shifting and focusing their attention and is associated with less hostile, controlling, or over-reactive parenting (Bridgett et al, 2009; Morrell & Murray, 2003). Surgency/extraversion, hereafter referred to as surgency, reflects the extent to which children express high intensity positive affect and are active, impulsive, stimulation-seeking, and social; this dimension has been linked to less sensitive or more negative parenting (Karreman, de Haas, van Tuijl, van Aken, & Deković, 2010; Planalp et al, 2013). However, it should be noted that positive emotionality, an aspect of surgency, has been linked to fewer negative parenting practices (Bridgett, Laake, Gartstein & Dorn, 2013).…”
Section: Introductionmentioning
confidence: 99%